The Effect of Socioeconomic Status and Anomie on Illegal Behavior - Aljbour, Rami Abed AL-Hameed; Wraikat, Ayed (Jordan Journal of Social Sciences, 2024)
The study aims at identifying the impact of the socio-economic status and anomie on the tendency toward the illegal/ deviant behavior. A social survey method was used, the questionnaire consisted (3) parts An Organized random sample consisted of (328) students from Ajloun University College were selected. The results of the study showed that the impact of the socio-economic status on the tendency toward the deviant behavior was an average of (3.521%). The results also showed that the effect of anomie on the tendency toward the deviant behavior was mid and with an arithmetic mean of (3.318%). The results showed that gender and age have no role in the impact of socio-economic status and anomie toward the deviant behavior. The existence of significant statistical differences concerning monthly income and deviant behavior implies that the increase of monthly income reduces the propensity toward deviant behavior and vice versa. Based on the results, the researchers provide many recommendations related to the questions of the study.